Uses and potential of mobile devices in francophone sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Nowadays, the proliferation of Information and Communication Technologies (ICT), their constant evolution and the diversity of services offered are generating a craze but also raise questions about the scope of possibilities. The adoption and development of the use of these mobile devices (cellphone, computer, internet) considerably transforms the individual's work postures by abolishing or reducing spatio-temporal boundaries (Besseyre des Horts & Isaac, 2006). DISTICs are now attributed an imaginary social "power" that the researcher cannot neglect (Flichy, 2001). Nevertheless, a critical approach makes it possible, with hindsight, to go beyond the accompanying discourses held by equipment manufacturers and international institutions as well as governments, to study in depth the sociology of uses, the contexts of uses as well as the stakes associated with them.In short, this would mean that there are technological devices that are being put in place in Africa, and more particularly in Niger, but which do not correspond to the expectations and needs of users, and so users reinvest them to do different things. For many manufacturers of communication machines, it is a matter of duplicating the Western model in Africa, but this cannot work in this way in Niger (Maïdakouale & Kiyindou, 2015). This is because there is a lack of data that concretely determines the expectations and needs of users. The original use of these systems is therefore subject to "tinkering" and "detour" by African users (de Certeau, 1990; Perriault, 1989).The data collected in this study is aimed essentially at "identifying uses" and highlighting users' expectations so that DISTICs can be successfully integrated into the socioeconomic fabric of Niger. Corpus processing system During this study, we conducted nearly 70 audio-visual interviews.The analysis of the first data collected was carried out using Advene software (for the transcription of the interviews) and Noo
Keywords: African Research